Different Levels of Context-Specificity of Teacher Self-Efficacy and Their Relations With Teaching Quality - Thommen, Désirée; Grob, Urs; Lauermann, Fani; Klassen, Robert M.; Praetorius, Anna-Katharina (Frontiers in Psychology, 2022)
On the basis of Bandura’s social cognitive theory, researchers often assume that a teachers' self-efficacy (TSE) will have a positive effect on teaching quality. However, the available empirical evidence is mixed. Building on previous research into TSE, we examined whether assessing class-/task-specific TSE gives a more accurate indication of the associations between TSE assessments and student-rated teaching quality. The analyses were based on the English sample of the TALIS Video Study. Mathematics teachers (N = 86) rated their self-efficacy beliefs using generalized task-specific TSE items and class-/task-specific TSE items. Their students (N = 1930) rated the quality of teaching in their math class. Multilevel regression analyses revealed stronger associations between student-rated teaching quality and class-/task-specific TSE than generalized task-specific TSE. We discuss possible reasons for these results and outline the potential benefits of using class-specific assessments for future TSE research.